Trade unions in an era of globalisation - Ragoobur, Satiumsingh (2004)
The objectives of this thesis are twofold. First, to investigate the link between foreign competition and the decline of unionisation in Britain during the 1980s and early 1990s. Second, to examine the impact of international trade on the wage bargaining strength of trade unions as measured by the union wage gap of individual workers.